Mobile robot navigation with planned path using internal sensors [electronic resource] - Ariff Azraai Roslan, 1992- , author; Rosbi Mamat (2015)
Project Paper (Sarjana Muda Kejuruteraan (Elektrik - Mekatronik)) - Universiti Teknologi Malaysia, 2015